Internal control system in the public management of a small municipality (Revista Brasileira de Contabilidade e Gestão, 2018)
The objective of this work is to analyze internal control in the public management of a small municipality from three perspectives: (i) controller profile, (ii) internal control situation, and (iii) planning and execution of activities, and verify, if all of these are adherents to the legal regiment and are close to the reality of other municipalities already studied. The potential problem of internal control in the public management of small municipalities, highlighted by Castro (2013), is that in these prefectures, there is a tendency to centralize tasks in the same person, which is corroborated by previous work. However, few of these studies analyze the dynamics of internal control in small municipalities. In methodological terms, the research had a qualitative nature, a descriptive. In the data collection, in turn, a questionnaire was used,with 19 questions, elaborated from the work of Roza, Lunkes and Alberton (2012) and Vieira (2009), and applied to the internal control officer of the city council in evidence. The main results of this research indicate that the internal control system of the studied municipality is very much in line with the profile of other prefectures evidenced by the work developed previously. The main results suggest that internal control operates in several areas, it aids in the planning and development of municipal public management, however, to the points to be improved, it is suggested the hiring of career servers, as well as periodic and punctual training.
Keywords: management; internal control; municipal public management